Spicy food for the egg-cowries: the evolution of corallivory in the Ovulidae (Gastropoda: Cypraeoidea) - Nocella, Elisa; Zvonareva, Sofya Sergeevna; Fassio, Giulia; Pica, Daniela; Buge, Barbara; Villa, Raimondo; Puillandre, Nicolas; Modica, Maria Vittoria; Oliverio, Marco (Frontiers in Marine Science, 2024)
Introduction Host-parasite associations provide very useful models to study adaptive processes. We investigated the interaction between carnivorous marine gastropods, the Ovulidae or egg-cowries, and their cnidarian food targets. Ovulidae (Fleming, 1828), is a family of specialized carnivorous caenogastropods that feed by browsing on octocorals (Anthozoa: Octocorallia: Malacalcyonacea and Scleralcyonacea) or, to a much lesser degree, on antipatharians (Anthozoa: Hexacorallia: Antipatharia) and Stylasteridae (Hydrozoa: Hydroidolina: Anthoathecata). Very scanty information is available on the phylogenetic relationships and the degree of specificity of the relationship with the cnidarians of this corallivorous lineage, especially for deep-water taxa. Methods To assess taxonomic identifications and investigate cnidarian/ovulid relationships in the context of their evolution, we generated an extensive molecular dataset comprising two mitochondrial (cox1 and 16S rDNA) and one nuclear gene (28S rDNA) from 524 specimens collected worldwide. The coral hosts of the ovulid species have been identified by integrating literature data with new records, employing morphological and/or molecular (the mitochondrial 16S rDNA and mtMSH, and the nuclear ITS2) markers. Results We obtained a molecular phylogenetic framework for the Ovulidae, time-calibrated with nine reliable fossil records. An ancestral state reconstruction allowed to identify Hexacorallia or Hydroidolina as the most likely ancestral cnidarian host for the Ovulidae. Discussion Our phylogenetic hypothesis revealed the existence of groups that do not completely correspond to the currently employed subfamilial arrangement. Concerning trophic ecology, while only pediculariines (Pedicularia and allied) are associated with hydrozoans (Stylasteridae), our results suggest that some ovulid lineages shifted independently between octocorals and hexacorals.